A COMPREHENSIVE ANALYSIS OF OTT PLATFORM REGULATIONS IN INDIA - 1. Dr. Priyadarshi Nagda , 2. Mrs. Neha Maheshwari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
OTT platforms have changed how people in India consume entertainment by providing easy access to a wide variety of content. However, their rapid growth has brought challenges. Unlike traditional media like TV and movies, which are strictly regulated, OTT platforms have little oversight. This allows for creative freedom but also exposes viewers, especially children, to harmful content like extreme violence, nudity, and controversial themes. India has started addressing these issues through rules like the IT Rules 2021 and the proposed Broadcasting Services Regulation Bill, 2023. These introduce measures like content classification, self-regulation by platforms, and penalties for violations. However, challenges like unclear jurisdiction between government bodies and the lack of a proper certification system remain. This article explores how OTT platforms have grown, the problems they bring, and the steps needed to regulate them without stifling creativity. Striking the right balance between freedom and accountability is key to ensuring that these platforms continue to thrive while respecting cultural and societal values.